Evaluation of anti-bacterial activity of ethanolic extract of genus piper sp. (Funded work) - ROSYE H. R. TANJUNG; YOHANIS NGILI (International Journal of Pharma and Bio Sciences, 2019)
Genus Piper sp that grows naturally in the province of Papua has been reported for its various medicinal uses. Research using natural Papuan materials and their exploration for drug manufacturing is frontier research and is on the frontline of science for drug discovery studies. The present study was planned to determine the chemical components present in the ethanolic extract of Genus Piper spand to evaluate the anti-bacterial activity. The DNA of several pathogenic bacteria, such as Escherichia coli, Salmonella typhimurium, and Salmonella typhi were interacted with the extract and the activity was compared. The inhibition of bacterial growth was seen through testing by two methods, the agar diffusion method and the colony count method. The results showed that the ethanol extract of Piper sp genus from dried powder had the antibacterial activity of Salmonella paratyphi type A, B, C, D, and E with an inhibition area of 11 mm, 14.5 mm, 14 mm, 13 mm and 10 mm respectively. While the percentage of inhibition of single colonies were found to be 71.27%, 20.32%, 77, 03%, 45.93% and 15.54% respectively. This study opens a new paradigm for collaboration across disciplines, such as mole biology economics, microbiology, biochemistry, clinical pharmacy, and related fields.